Evaluation of anti-candida effect of ozonated water on Candida strains: An in vitro study - Semyari, Hassan; Mehrnia, Nika; Yaghoubi, Hamid (Student Research in Translational Medicine, 2022)
Abstract Background and aim: Oral candidiasis is an opportunistic and common infection in the oral cavity. It is caused by the overgrowth of Candida albicans species. The prevalence of this infection varies according to gender and other predisposing factors. Ozone therapy is one of the modern and new non-pharmacological treatments and so far, many antimicrobial and antifungal effects of ozonated water have been reported. Materials and Methods An ozone gas generator was used to prepare ozonated water. After turning on the generator, its connector hose was placed in a graduated cylinder containing yeast suspension (at 0.5 McFarland turbidity). Then the generator was turned on for 15 minutes and at 0 seconds, 15 seconds, 30 seconds, 3 minutes, 5 minutes, 10 minutes and 15 minutes the graduated cylinder was sampled and cultured in Sabouraud agar medium. Samples incubated for 48 hours. After incubation the colonies were counted and the effect of ozonated water was examined. Results Ozonized water completely destroyed all Candida colonies in a short time (15 seconds). Conclusion The antifungal activity of ozonated water seems to depend on the duration of its exposure to Candida yeast and ozonated water can destroy Candida colonies in a short time.